2009
DOI: 10.1016/j.cmet.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of ARNT/HIF1β in Liver Alters Gluconeogenesis, Lipogenic Gene Expression, and Serum Ketones

Abstract: In preparation of the paper, there were several errors in the figure labeling, which were regretfully missed in the preparation and proofreading of the manuscript and which the authors would like to correct. None of these changes affects the data or the conclusions of the paper.(1) The heading of Figure 2H should read ''Glucose Infusion Rate,'' not ''Insulin Infusion Rate.'' (2) In the corresponding text on page 431 (right column, paragraph 2, line 13), the units for glucose infusion rate should be ''mg/kg/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…These data are corroborated in mice where it was demonstrated that ARNT suppression severely impairs the insulin release in response to glucose, as well as other features resembling those observed in diabetic humans (Gunton et al, 2005;Wang et al, 2009). Is ARNT deficiency a cause or a consequence of the pathological changes of diabetes?…”
Section: Arnt As a Modulator Of Er Activitysupporting
confidence: 80%
“…These data are corroborated in mice where it was demonstrated that ARNT suppression severely impairs the insulin release in response to glucose, as well as other features resembling those observed in diabetic humans (Gunton et al, 2005;Wang et al, 2009). Is ARNT deficiency a cause or a consequence of the pathological changes of diabetes?…”
Section: Arnt As a Modulator Of Er Activitysupporting
confidence: 80%
“…A key question is whether this is related to regulation of HIF function, or to altered activity of other putative FIH targets. Loss of VHL in hepatocytes results in a severe HIF-dependent steatosis, and deletion of HIF-1β in liver results in increased hepatic gluconeogenesis and lipogenic gene expression but reduced hepatic lipid storage (Rankin et al, 2009; Wang et al, 2009). These data indicate that HIF activation increases steatosis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Further, HIFs regulate major metabolic liver functions, and in particular studies in which either ARNT or the two HIFα subunits were deleted supported this. Liver-specific ablation of the common beta HIF subunit (ARNT) in mice increased fed insulin levels, gluconeogenesis, lipogenesis, and decreased ketone bodies [45]. Deletion of HIF-1α was shown to impair gluconeogenesis during liver regeneration [46] whereas HIF-2α was crucial for hepatic insulin signaling [47] and accordingly its constitutive activation in mouse liver resulted in development of severe hepatic steatosis associated with impaired fatty acid beta-oxidation, decreased lipogenic gene expression, and increased lipid storage capacity [48].…”
Section: Hypoxia-inducible Transcription Factors (Hifs)mentioning
confidence: 99%